Counterion-directed approach to the Diels-Alder paradigm: cascade synthesis of tricyclic fused cyclopropanes - Kiss, E; Campbell, C; Driver, R; Jolliffe, J; Lang, R; Sergieiva, T; Okovytyy, S; Paton, R; Smith, M (Wiley, 2016)
An approach to the intramolecular Diels-Alder reaction has led to a cascade synthesis of complex carbocycles composed of three fused rings and up to five stereocentres with complete stereocontrol. Computational analysis reveals that the reaction proceeds via a Michael-Michael-cyclopropanation-epimerization cascade, in which size and coordination of the counterion is key.